2022
DOI: 10.1097/bot.0000000000002248
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric and Adolescent Fractures of the Acetabulum Treated With ORIF: What Are Their Functional Outcomes?

Abstract: Objectives:To evaluate the functional outcomes of pediatric and adolescent patients (<18 year old) who sustained acetabulum fractures that were treated with open reduction internal fixation (ORIF).Design:Retrospective cohort.Setting:Level 1 trauma center.Patients:Thirty-four pediatric and adolescent patients underwent acetabulum fracture ORIF between 2001 and 2018. Of the operatively treated patients, 21 patients had sufficient follow-up (>6 months), one died after fixation secondary to other traumatic injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In terms of treatment, both non-surgical and surgical management of pediatric acetabulum fractures using adult indications has resulted in acceptable clinical and radiographic outcomes. 37,43,44,[58][59][60]…”
Section: Discussionmentioning
confidence: 99%
“…In terms of treatment, both non-surgical and surgical management of pediatric acetabulum fractures using adult indications has resulted in acceptable clinical and radiographic outcomes. 37,43,44,[58][59][60]…”
Section: Discussionmentioning
confidence: 99%
“…In adolescent patients with growth remaining, the principles of acetabular fixation involve anatomical reduction and insertion of screws [7 ▪ ] or contoured plates, with hardware typically removed [4,27] following healing in order to minimize growth disturbance. Skeletally mature patients can be treated as adults with acceptable clinical and radiographic outcomes [8,37]. In rare cases, total hip arthroplasty has been employed for adolescents with an unsalvageable joint [7 ▪ ].…”
Section: Definitive Managementmentioning
confidence: 99%
“…Southam et al reported on pediatric and adolescent acetabular fractures treated with open reduction and internal fixation. Eighteen (86%) of 21 patients had a favorable functional outcome, although 2 patients with a delayed reduction (>6 hours) of a fracture-dislocation developed osteonecrosis 63 . Griffith et al reviewed patients with sickle cell disease who had a mean age of 14 years and were undergoing core decompression with a bone marrow aspirate concentrate injection for femoral head osteonecrosis.…”
Section: Hip Preservationmentioning
confidence: 99%